Clostridium difficile infection risk in patients with hidradenitis suppurativa. (1st November 2022) - Sanghvi, Anuj Pranav; Miles, J. Alex; Sayed, Christopher
Abstract: Widespread use of antibiotics for hidradenitis suppurativa (HS) opens up the possibility of Clostridium difficile infection (CDI) and an increased risk of mortality. The purpose of this study was to identify risk factors for acquiring CDI in patients with HS. We suggest that providers should take risk factors including increased antibiotic class, hospitalizations, and advanced patient age into consideration when prescribing antibiotics for HS.